A STUDY ON THE SOUND SHIFT IN THE ENGLISH BORROWINGS USED IN SUARA MERDEKA NEWSPAPER - SETIAWAN, GUNTUR TRI INDRA (2007)
In globalization era, people need to master more than one language (bilingualism or multilingualism). One of the effects of bilingualism is borrowing. People borrow some words from other languages when they can not find the appropriate words in their conversation. In particular, in this research, the researcher uses Suara Merdeka newspaper as the data source. The objective of the this research are to describe the type of the sound shift which are found in English borrowings in Suara Merdeka and to describe the kinds of sound which are used in replacing the English words. The researcher uses many theories of phonological process from Katamba, and theory of borrowing from Mestrie and Leap. The type of this research is descriptive qualitative method. In collecting the data, the writer applied the reading and collecting. The several steps are done to analyze the data. In analyzing the forms of borrowing words, the steps are: describing the phonological conditioned form of borrowing words used in Suara Merdeka newspaper. This means that the data being classified are analyzed phonologically. This research shows the types of sound shift which are found in English borrowings used in Suara Merdeka Newspaper. At least, there are three types of sound shift. They are Front, Middle and End shift. The Indonesian speakers prefer to pronounce the borrowing words based on the phoneme of the word than imitate how the native speaker of English pronounced the words. For example, the word april [ei prl] in English shift become april [april] in Indonesian language. This research also describes the kinds of sound used to replace the English borrowings. The result of the analysis is presented in both forms formal and non-formal presentation. The researcher uses formula while in non-formal, the researcher uses description.